Decolonizing costume: Unpicking ballet's racist and colonialist stereotypes through Sidney Nolan's costumes for The Rite of Spring (1962). Issue 1 (1st May 2022) - Collett, Emily
This article attempts to unpick colonialist and racist stereotypes in costume, in an effort to think through decolonization in relation to costume design and research. Examining Sidney Nolan's costumes for the Royal Ballet's 1962 production of The Rite of Spring, which misappropriated Australian First Nations cultures for visual (and choreographic) inspiration, the primary aims are to articulate the complexities of the production's oppressive colonial roots, and to situate it within the wider context of recent challenges from scholarship and discourse around traditional ballet that have reframed it as a potentially racist art form. The discussion positions the costumed dancers from this production in relation to problematic binaries articulated more recently in scholarship around modern dance. A consideration of the damaging perpetuation of stereotypes the costumes propagate offers a way of understanding the ongoing impact of ballet's colonialist history, and the role costume (and those who create it) plays in this.